Prospects for peace among the fraternities in the University of the Philippines in the Visayas, Miag-ao Campus - Calimoso, Lyndon F.
The study sought to identify the areas and factors that have, or have the potential to cause tension in the relations of the fraternities, identify the factors thaqt have the potential to promote peace in the relations of the fraternities and to look into the question of what International relations maybe applied to the interactions of the fraternities to lessen or prevent tension.